(untitled) - Douglas A Rund (St. Louis, Missouri, 1996)
The book includes sixty-eight succinct chapters that are arranged into six parts: general concepts, signs ans symptoms, trauma, environmental emegencies, systemic disorders, and special problems. The symptoms, signs, and conditions discussed include common emergency conditions, and situations in which appropriate emergency treatment makes a critical difference in outcome. The book presents in-depth coverage of the concepts of the clinical practice and pathophysiology of emergency medicine
Keywords: emergency medical service,medical emergencies,rescue work